THE ROLE OF IVAN FRANKO IN THE FORMATION OF THE PARADIGM OF THE UKRAINIAN FINANCIAL SYSTEM - KRUPKA, Myhaylo; BODAKOVSKYY, Volodymyr (Scientific journal «World of Finance», 2024)
Introduction. The article is devoted to the theoretical and conceptual ideas of I. Franko. A scientific study of the main paradigms in the works and publications of the famous Ukrainian scientist is carried out, namely in the field of functioning of the financial environment of society, information is provided from the standpoint of understanding the evolutionary nature of the formation of approaches to the interpretation of the historical development of financial science. In order to obtain proper scientific results in the study of Franko’s scientific work, the main scientific methods were used, namely empirical ones – to reassess the macro-financial analysis of the budgetary sphere of Galicia of the XIX–XX centuries; theoretical – for the projection of the scientist’s ideas on the modern theoretical and applied realities of the functioning of society; synthesis – to identify relevant concepts for improving the country’s financial system; abstraction – to identify the key directions and warnings of the great Ukrainian thinker regarding the financial and political development of society; generalization – for the formation of timely authoritative proposals of I. Franko, which strengthen the financial paradigms of modern financial scientists working on research of the financial environment of society, and the formation of key proposals for improving its institutions in conditions of uncertainty. The purpose of the article is to generalize the scientific heritage of I. Franko in order to reassess the main paradigms of the functioning of the modern financial system of Ukraine. Results. The main ideas and debatable issues related to the functioning of the country’s financial system on the territory of Galicia during the period of the Austro-Hungarian Empire, especially the budgetary sphere, the business environment and the financial capacity of individuals, are allocated. Ivan Franko’s approach to the study of financial relations and detailing of financial analysis at all levels of the economic system has been updated, which allows us to assert a significant contribution of the scientist to the development of macro-financial analysis. The main problems identified by the scientist in his research are considered and his own scientific vision for the prospects and proper adaptation of scientific proposals is formed. Conclusions. Based on the carried out research, the need to strengthen the role of higher education institutions, the mechanism for balancing budget revenues and expenditures and the financial and legal policy of social direction to strengthen the sovereignty of Ukraine and the development of its financial system is proposed and substantiated.